Heart healthy diet and risk of myocardial infarction and venous thromboembolism - Hansen-Krone, Ida J.; Enga, Kristin F.; Njølstad, Inger; Hansen, John-Bjarne; Braekkan, Sigrid K. (Thrombosis and Haemostasis, 2012)
Prudent dietary patterns are associated with reduced risk of arterial cardiovascular diseases (CVD). Limited data exist on the relation between diet and venous thromboembolism (VTE). The aim of our prospective, population based study was to investigate the association of a heart healthy diet on risk of myocardial infarction (MI) and VTE. Information on dietary habits was available in 18,062 subjects, aged 25–69, who participated in the fourth Tromsø study, 1994–1995. Dietary patterns were assessed by a slightly modified version of the validated SmartDiet score; a 13-item questionnaire producing a diet score based on the intakes of fat, fibre, fruit and vegetables. Incident events of MI (n=518) and VTE (n=172) were recorded to the end of follow-up December 31, 2005 (median follow-up 10.8 years). Cox-regression models were used to calculate hazard ratios (HR). A healthy diet score of >27 points (upper tertile) was associated with 17% reduced risk of MI (HR: 0.83, 95% confidence interval [CI]: 0.66–1.06), and no association with VTE (HR: 1.01; 95%CI: 0.66–1.56), compared to <24 points (lower tertile) in multivariable analysis. High intake of fish, fruit, vegetables and polyunsatured fat had a 23% reduced risk of MI (HR 0.77; 95%CI: 0.60–0.98), but no association with VTE (HR 0.95; 95%CI: 0.64–1.40). A heart healthy diet showed an even more favourable association with MI in obese subjects (HR: 0.62; 95%CI: 0.41–0.95), but not with VTE. Our findings suggest that a heart healthy dietary pattern is associated with moderately reduced risk of MI, but not related to risk of VTE.
Keywords: Venous thrombosis; risk factors; nutrition